Implementation of the "Ayo Ke Sinjai" Application as a Communication Media for the Sinjai Regency Tourism and Culture Office - M. Erwin Syukri; Amrullah Nur (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
This study examines the implementation of the “Ayo Ke Sinjai” application as a communication medium for the Sinjai Regency Tourism and Culture Office. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation. Findings show that the application has not functioned effectively as an official communication channel. Public adoption is low, and residents prefer social media to obtain tourism updates. This gap is largely attributable to ineffective socialization: promotional efforts concentrated on stakeholders during the launch and initial dissemination, without sustained engagement or broad targeting of community groups who are the primary users and evaluators of the information system. From a management perspective, capacity-building is required to ensure routine, effective application administration. Training for staff must be supported by a dedicated budget to cover maintenance, updates, and troubleshooting. Without these resources, the application risks remaining dormant and failing to deliver its intended public service. To address these shortcomings, the Tourism and Culture Office should commit to reactivating “Ayo Ke Sinjai” as a central hub that integrates tourism activities and simplifies access to information. Priority actions include strengthening management resources, instituting regular content and feature updates, and embedding user feedback mechanisms so the public can provide suggestions and report issues directly within the app. Complementary outreach should leverage both online and offline channels, partnering with communities, schools, MSMEs, and local creators to drive adoption. With sustained commitment, adequate funding, and participatory engagement, “Ayo Ke Sinjai” can evolve into an effective two-way communication platform for Sinjai’s tourism ecosystem.